(untitled) (Web of Teachers: Inderscience Research, 2024)
This article assumes the task and content of spiritual moral education of children of preschool age to educate and develop the spiritual world of the child, his consciousness, moral feelings, personal qualities. Education of moral feelings, attitudes and behavior in children. Giving moral knowledge performs a number of educational tasks, gives a wide picture, concepts about the moral values of human life and culture.